Noble gases solubility models of hydrocarbon charge mechanism in the Sleipner Vest gas field - Barry, P; Lawson, M; Meurer, W; Warr, O; Mabry, J; Byrne, D; Ballentine, C (Elsevier, 2016)
Noble gases are chemically inert and variably soluble in crustal fluids. They are primarily introduced into hydrocarbon reservoirs through exchange with formation waters, and can be used to assess migration pathways and mechanisms, as well as reservoir storage conditions. Of particular interest is the role groundwater plays in hydrocarbon transport, which is reflected in hydrocarbon-water volume ratios. Here, we present compositional, stable isotope and noble gas isotope and abundance data from the Sleipner Vest field, in the Norwegian North Sea. Sleipner Vest gases are generated from primary cracking of kerogen and the thermal cracking of oil. Gas was emplaced into the Sleipner Vest from the south and subsequently migrated to the east, filling and spilling into the Sleipner Ost fields. Gases principally consist of hydrocarbons (83-93%), CO2 (5.4-15.3%) and N2 (0.6-0.9%), as well as trace concentrations of noble gases. Helium isotopes (3 He/4 He) are predominantly radiogenic and range from 0.065 to 0.116 RA; reported relative to air (RA = 1.4 x 10-6 ; Clarke et al., 1976; Sano et al., 1988), showing predominantly (>98%) crustal contributions, consistent with Ne (20Ne/22Ne from 9.70-9.91; 21Ne/22 Ne from 0.0290- 0.0344) and Ar isotopes (40Ar/36Ar from 315-489). Air-derived noble gas isotopes (20Ne, 36Ar, 84Kr, 132 Xe) are introduced into the hydrocarbon system by direct exchange with air-saturated water (ASW). The distribution of air- derived noble gas species are controlled by phase partitioning processes; in that they preferentially partition into the gas (i.e., methane) phase, due to their low solubilities in fluids. Therefore, the extent of exchange between hydrocarbon phases and formation waters – that have previously equilibrated with the atmosphere – can be determined by investigating air-derived noble gas species. We utilize both elemental ratios to address process (i.e., open vs. closed system) and concentrations to quantify the extent of hydrocarbon-water exchange (i.e., volumetric gas-water ratios). These data are discussed within the framework of several conceptual models: i) Total gas- stripping model, which assumes all noble gases have been stripped from the water phase, thus defining the minimum volume of water to have interacted with the hydrocarbon phase; ii) Equilibrium model, which assumes equilibration between groundwater and hydrocarbon phase at reservoir P, T and salinity; and iii) Open and closed system gas-stripping models, using concentrations and elemental ratios. By applying these models to Ne-Ar data from Sleipner, we estimate volumetric gas-water ratios ( Vg Vw ) between 0.02-0.07, which are lower than standard geologic gas-water estimates of ~0.24, estimated by combining gas-in-place estimates with groundwater porosity estimates. Sleipner Vest data can be best approximated by an open system model, which predicts more than an order of magnitude more groundwater interaction during migration than geologic estimates, indicating a dynamic aquifer system and/or a hydrous migration pathway. In an open system, the extent of gas loss can be estimated to be between 8-10 reservoir volumes, which have passed through the system and been lost (i.e., filled and spilled).